Insecticidal activities of diketopiperazines of Nomuraea rileyi entomopathogenic fungus - Marcinkevicius, Karenina (2017)
Entomopathogenic fungi are fungal organismsextensively used in various parts of the world asbiopesticides against insect pests that cause importanteconomic damage. Various secondary metabolitesproduced by these fungi have many potential biologicalactivities. The present study was undertaken to evaluatethe insecticidal activity of extracts and pure compoundsfrom Nomuraea rileyi (Farlow) Samsonentomopathogenic fungi against Spodoptera frugiperdaSmith (Lepidoptera), Ceratitis capitata Wiedemann(Diptera) and Tribolium castaneum Herbst (Coleoptera),three insect pests that generate serious economic losses inthe northwest of Argentina. Diketopiperazines wereextracted from the culture free supernatant of the mediawith ethyl acetate. Antifeedant properties were detected inall extracts under dietary choice conditions (300 ug/ g ofdiet). The maximum antifeedant activity was noted incycles (Pro-Val) (86.02) and cycle (Pro-Phe) (73.47),while the rest of the extracts and metabolites exhibitedvarying degrees of moderate or less toxic effects. Themaximum oviposition deterrence against C. capitata(55.86%) was recorded with cycle (Pro-Phe) at a 50µm/cm2 dose. Culture medium extracts supplementedwith insect remains and all pure compounds showedrepellent action against T. castaneum. The mainrepellency was observed in phenylacetic acid and cycle(Pro-Val) with RI values of 42 and 41% respectively. Thepresent study would suggest the possible utilization ofentomopathogenic fungal metabolites as an effectiveagent for controlling insect pests that cause importanteconomic losses.